Causal network models of SARS-CoV-2 expression and aging to identify candidates for drug repurposing - Anastasiya Belyaeva (Nature Portfolio, 2021)
Given the severity of the SARS-CoV-2 pandemic, a major challenge is to rapidly repurpose existing approved drugs for clinical interventions. Here, the authors identify robust druggable protein targets within a principled causal framework that makes use of multiple data modalities and integrates aging signatures.